Pipeline transport applications : Newtonian and non-Newtonian fluids - Stearns, Jim (Knovel, 2013)
"Pipelines are a practical means of providing long-distance transport of water, fuels, and in particular, water-based slurry suspensions of metals and minerals along with their by-products. When designing pipeline networks it is important to consider the types of fluids that might be moved through them. Materials can be broadly categorized as being either Newtonian (homogeneous and uniform, such as water and gasoline), or non-Newtonian (either homogeneous or heterogeneous with variable composition, such as paint, gelatin, or slurries), and each type of material has specific qualities that must be considered in order to ensure that the pipeline will function as designed."--Description at Knovel website.